2017
DOI: 10.1590/0100-3984.2016.0167
|View full text |Cite
|
Sign up to set email alerts
|

Tomographic aspects of penetrating thoracic trauma: injuries from firearms and other weapons

Abstract: ObjectiveThe aim of this study was to analyze the various computed tomography findings in penetrating chest trauma, as well as to determine the frequency and extent of the lesions.Material and MethodsWe studied the computed tomography findings from 40 cases of penetrating thoracic trauma, of which 35 (85.8%) were gunshot wounds and 5 (14.2%) were caused by another type of weapon.ResultsPulmonary lesions were found in 39 cases (97.5%), manifesting as contusions in 34 cases (85%), atelectasis in 8 (20%), lacerat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0
13

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(26 citation statements)
references
References 19 publications
0
13
0
13
Order By: Relevance
“…Los hallazgos y/o lesiones torácicas más frecuentes fueron el hemotórax no masivo, neumo-tórax, contusión pulmonar y enfisema subcutáneo. Esto se condice con la literatura donde las lesiones pulmonares son las más frecuentes 3,17,26 . Cabe mencionar que los TPC corresponden a un 10,2% de los TTAF y que estos forman parte de una entidad distinta, con características propias y mayor mortalidad 25 .…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Los hallazgos y/o lesiones torácicas más frecuentes fueron el hemotórax no masivo, neumo-tórax, contusión pulmonar y enfisema subcutáneo. Esto se condice con la literatura donde las lesiones pulmonares son las más frecuentes 3,17,26 . Cabe mencionar que los TPC corresponden a un 10,2% de los TTAF y que estos forman parte de una entidad distinta, con características propias y mayor mortalidad 25 .…”
Section: Discussionunclassified
“…Se requirió de tratamiento invasivo en la mayoría de los pacientes (77,6%), correspondiendo en su mayoría a pleurotomía (42,9%). Series europeas describen tratamiento suficiente con pleurotomía en el 76,3% de los casos [22][23][24][25][26][27] . La necesidad de cirugía torácica descrita en distintas revisiones oscila entre 5,8%-71,0% 17,28 , esto se puede deber a las diferencias epidemiológicas en las distintas poblaciones, además, la mayoría de los estudios incluyen grupos heterogéneos de lesiones como las toracoabdominales.…”
Section: Discussionunclassified
“…(Nummela et al, 2019) SW are the most prevalent cause of surgical intervention of PCI (39-81.4%) (Uchimura et al, 2010;Karigyo Toshiyuki et al, 2013;Besir, Gokalp and Eygi, 2015;Khorsandi et al, 2015), even though GSW has been reported as the main etiology of PCI, it often presents higher mortality rate prior to the arrival into the OR. (Albadani and Alabsi, 2013;Kaljusto et al, 2015;Melo et al, 2017;de Araújo et al, 2018)…”
Section: Prognosismentioning
confidence: 99%
“…8 The impact of the study has been seen on the management of both civilian and military populations in the United States and abroad. [9][10][11] The ripple effect of this article extends well past the management of the TMGSW patient. With the success of CT scanning as a screening tool for hemodynamically stable patients with a TMGSW, CT scan use for penetrating injury was expanded sequentially to other truncal locations including the flank, pelvis, and thoracoabdominal region.…”
mentioning
confidence: 99%
“…8 The impact of the study has been seen on the management of both civilian and military populations in the United States and abroad. 9-11…”
mentioning
confidence: 99%